2000
DOI: 10.1152/ajplung.2000.278.1.l25
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of GM-CSF increase by diesel exhaust particles in human airway epithelial cells

Abstract: We have previously shown that exposure to diesel exhaust particles (DEPs) stimulates human airway epithelial cells to secrete the inflammatory cytokines interleukin-8, interleukin-1beta, and granulocyte-macrophage colony-stimulating factor (GM-CSF) involved in allergic diseases. In the present paper, we studied the mechanisms underlying the increase in GM-CSF release elicited by DEPs using the human bronchial epithelial cell line 16HBE14o-. RT-PCR analysis has shown an increase in GM-CSF mRNA levels after DEP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 41 publications
7
73
0
Order By: Relevance
“…This observation is in agreement with previous studies that have shown that peroxynitrite may interfere with surfactant activity (20). Furthermore, we have previously shown that DEPs-induced effects in human airway epithelial cells are partly mediated through the production of reactive oxygen species (9). We hypothesized in the present study that DEPs-induced increase in PC might be mediated by reactive oxygen species of the NO pathway such as peroxynitrite.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This observation is in agreement with previous studies that have shown that peroxynitrite may interfere with surfactant activity (20). Furthermore, we have previously shown that DEPs-induced effects in human airway epithelial cells are partly mediated through the production of reactive oxygen species (9). We hypothesized in the present study that DEPs-induced increase in PC might be mediated by reactive oxygen species of the NO pathway such as peroxynitrite.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that PAHs, which are adsorbed on DEPs but not on carbon black particles, are responsible for the effects of DEPs. This observation is in agreement with previous reports, which have emphasized the specific PAHs' role in the DEPs activity in bronchial cells (9), macrophages (47), and ATII cells (24). This role of PAHs is corroborated by the observation that the catalysts that reduce the adsorbed organic compounds also reduce the DEPs-induced increase in cytokine secretion by bronchial cells (8).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, activation of NF-B by DEP has been shown to regulate IL-8 and granulocyte-macrophage colony-stimulating factor expression in bronchial epithelial cells (9,57). Similarly, activation of Nrf2 transcription factor, which plays a critical role in the regulation of antioxidant enzyme expression (38), has been correlated with the induction of phase II detoxifying enzymes in bronchial epithelial cells in response to DEP (6).…”
mentioning
confidence: 99%
“…Adsorbed organic compounds have been implicated in many of the systemic and molecular responses of respiratory system cells exposed to diesel exhaust particles (3)(4)(5)(6). Studies with residual oil fly ash (ROFA) particles have demonstrated a role for particleassociated metals in inducing inflammatory responses in respiratory cells (7,8).…”
mentioning
confidence: 99%